Marketing, Technological Problems and Personal Barriers of Micro Enterprises - Karki, Bir Bahadur (Janapriya Journal of Interdisciplinary Studies, 2020)
Micro enterprise is a small scale enterprise which is established with the maximum capital of twenty hundreds thousands rupees except land & building and less than nine employees including the micro entrepreneur. Most of the micro enterprises are operating with a little fund, local resources and local skills. Main objective of the study is to identify marketing and technology related problems as well as personal barriers of micro enterprise in Baglung and Parbat districts. This study is based on mixed research design (quantitative and qualitative research). Data and information are collected through primary sources. Primary data are collected through structured questionnaires, focus group discussions, observations and field visits. Purposive and convenience sampling methods are used for selecting enterprises and entrepreneurs respectively. A few statistical tools such as percentage are used for data analysis. After the field visit of micro enterprises in Parbat and Baglung district and focus group discussion with micro enterprises, it is found that micro enterprises have been facing various types of problems. Micro enterprises have been facing various problems such as marketing related problems and technological related problems and personal barriers. Highly competitive markets, too far the market places, too small market size of the markets, machine and equipment not easily available, difficulty in identifying appropriate technologies, technologies to being changed very fast, lack of training/skills, lack of trust and cooperation, lack of experience and patience are the major problems faced by the enterprises.